Discovery of a Positive Allosteric Modulator of Cholecystokinin Action at CCK1R in Normal and Elevated Cholesterol - Harikumar, Kaleeckal G.; Coudrat, Thomas; Desai, Aditya J.; Dong, Maoqing; Dengler, Daniela G.; Furness, Sebastian G. B.; Christopoulos, Arthur; Wootten, Denise; Sergienko, Eduard A.; Sexton, Patrick M.; Miller, Laurence J. (Frontiers in Endocrinology, 2021)
Drugs useful in prevention/treatment of obesity could improve health. Cholecystokinin (CCK) is a key regulator of appetite, working through the type 1 CCK receptor (CCK1R), however, full agonists have not stimulated more weight loss than dieting. We proposed an alternate strategy to target this receptor, while reducing likelihood of side effects and/or toxicity. Positive allosteric modulators (PAMs) with minimal intrinsic agonist activity would enhance CCK action, while maintaining spatial and temporal characteristics of physiologic signaling. This could correct abnormal stimulus-activity coupling observed in high cholesterol environment observed in obesity. We utilized high throughput screening to identify a molecule with this pharmacological profile and studied its basis of action. Compound 1 was a weak partial agonist, with PAM activity to enhance CCK action at CCK1R, but not CCK2R, maintained in both normal and high cholesterol. 10 µM Compound 1 did not exhibit agonist activity or stimulate internalization of CCK1R. It enhanced CCK activity by slowing the off-rate of bound hormone, increasing its binding affinity. Computational docking of Compound 1 to CCK1R yielded plausible poses. A radioiodinatable photolabile analogue retained Compound 1 pharmacology and covalently labeled CCK1R Thr211, consistent with one proposed pose. Our study identifies a novel, selective, CCK1R PAM that binds to the receptor to enhance action of CCK-8 and CCK-58 in both normal and disease-mimicking high cholesterol environments. This facilitates the development of compounds that target the physiologic spatial and temporal engagement of CCK1R by CCK that underpins its critical role in metabolic regulation.